(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article explores the use of role plays as an effective strategy for developing students’ speaking competence in language learning. Speaking is a crucial skill in language acquisition, yet many students struggle with fluency, confidence, and communicative effectiveness. Role-playing activities provide a structured yet flexible environment where students can practice real-life communication, engage in meaningful dialogues, and enhance their interaction skills. The article reviews relevant literature on role plays in language teaching, presents sample role-play activities, and discusses their benefits in fostering speaking proficiency.